2014
DOI: 10.1007/s00264-014-2614-5
|View full text |Cite
|
Sign up to set email alerts
|

National trends and perioperative outcomes in primary and revision total shoulder arthroplasty

Abstract: This study demonstrates that the rate of TSA is rapidly increasing in the US, with over a four-fold increase in revisions and five-fold increase in primaries over the ten years studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 23 publications
2
31
1
Order By: Relevance
“…The increase in the utilization of shoulder arthroplasty observed is consistent with studies of other cohorts . Kim et al noted a 2.5‐fold increase in shoulder arthroplasty between 1998 and 2008 utilizing the US Nationwide Inpatient Sample.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The increase in the utilization of shoulder arthroplasty observed is consistent with studies of other cohorts . Kim et al noted a 2.5‐fold increase in shoulder arthroplasty between 1998 and 2008 utilizing the US Nationwide Inpatient Sample.…”
Section: Discussionsupporting
confidence: 81%
“…Shoulder arthroplasty has been increasingly utilized in the US over the past several decades . This trend will likely continue , and some have projected that the growth in demand for shoulder athroplasty may exceed that of hip and knee arthroplasty in the future .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors have documented the efficacy of anatomic TSA. It is one of the most rapidly growing procedures in the US, with over a fourfold increase in revisions and fivefold increase in primaries from 2001 to 2010 77,78. A 1982 review by Neer et al reported high satisfaction in all but 4 patients from a cohort of 194 shoulders managed with a minimally constrained TSA at a minimum 2-year follow-up 79.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, there were approximately 65,000 shoulder arthroplasties performed in the United States,6, 17 and the volume of this procedure is expected to continue to grow 5, 8. As a result, the number of revisions due to failures is also anticipated to increase 5, 19. The overall estimated rate of deep infection after shoulder arthroplasty is approximately 1% 15 .…”
mentioning
confidence: 99%